Physical oceanography from CTD stations conducted during RV ALKOR cruise AL575 in the North Sea - Schmidt, Mark; Haeckel, Matthias (PANGAEA, 2025)
Physical oceanographic parameters were recorded during Alkor cruise AL575 in the North Sea. Two CTD stations were conducted at 30.06.2022 and 11.07.2022, respectively. Data was measured and recorded by using a Seabird SBE9plus CTD. Water column data and near-seafloor profiles shall provide oceanographic baseline data in areas of potential offshore carbon storage sites.
Keywords: North Sea; oceanography